PENGARUH SUKU BUNGA OBLIGASI, IHSG, DAN PDB PERKAPITA TERHADAP PERMINTAAN OBLIGASI KORPORASI DI INDONESIA TAHUN 2004-2019 - Yoga, Syaputra Dwi; Syapsan, Syapsan; Any, Widayatsari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to determine how much influence the interest rates of bonds, IHSG and GDP per capita on demand for corporate bonds. This study uses an independent variable consisting of interest rates on bonds, IHSG and GDP per capita, with the dependent variable which is the demand for corporate bonds in Indonesia The data used in this study are annual data from 2004-2019. The analytical method used is descriptive quantitative and analyzed partially or simultaneously with multiple linear regression OLS (Ordinary Least Square) approach which is processed using E-Views version 9. From the test results show that the interest rates on bonds, IHSG, and GDP per capita together have a significant effect on demand for corporate bonds in Indonesia. Meanwhile, bond interest rates have a positive and significant effect on demand for corporate bonds, ihsg has a positive and significant effect on demand for corporate bonds in Indonesia and per capita GDP has a negative and not significant effect on demand for bonds in Indonesia. In addition, the value of adjusted R 2 was 89.22%.Keywords: Carporate Bond, Interest Rate Bond, Ihsg, GDP per Capita